Crafting High-Impact Entrepreneurial Orientation Research: Some Suggested Guidelines - Covin, Jeffrey G.; Wales, William J. (Entrepreneurship Theory and Practice, 2019)
Research on the topic of entrepreneurial orientation (EO) continues to proliferate. Nonetheless, the conceptualization and measurement of this construct are matters of ongoing discussion and debate, and construct-specific advice with respect to the generation high value-added EO research is sparse. This editorial is aimed at providing guidance to EO researchers in three areas: (a) EO’s conceptualization(s) and position as they relate to the larger set of corporate entrepreneurship-related constructs, (b) EO’s measurement challenges and possibilities, and (c) suggested guidance and directions for future EO research.